Study on Shapes, Colors and Ornaments According to Architecture Psychology: A Case Study of Roadside Buildings in Kitakyushu - Satrio Agung Perwira; Bart Dewancker (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2022)
Psychology in architecture is one that is highly considered in urban planning, or even smaller, the buildings in it. In this research, the study of shape, color, and ornament is the focus of the research. This research is a basic study for more in-depth research on the psychology of architecture in urban Kitakyushu. This study aims to study the shape, color, and ornamentation of buildings scattered in the center of urban growth in Kitakyushu. The survey results in this study will be assessed based on the theory of psychology in architecture. The method used in this research is a design and visual approach, with qualitative approaches. In the survey that has been carried out, it was found that the characteristics of Kitakyushu buildings are generally box-shaped with the use of natural colors, such as the color of the ground. This study also assumes that building design, color selection, and ornamentation affect urban vibes in Kitakyushu and directly affect the psychology of the people in it.